Theoretical and experimental studies on the interior ballistic of large UAV ejection based on trifluoromethane phase transition - Zhaijun Lu; Zhifu Wang; Shujian Yao; Mu Zhong; Kai Liu; Jiaqiang Wang (Scientific Reports)
Abstract Unmanned aerial vehicles (UAVs) have demonstrated immense value in the military sector. This research proposes the use of Trifluoromethane as a novel cold ejection medium. Trifluoromethane, being easily compressible, exhibiting high safety and low infrared characteristics, is well-suited for small-volume high-pressure chambers. The feasibility of Trifluoromethane for UAV ejection has been confirmed through experiment. Furthermore, a thermodynamic numerical model has been established for the ejection medium to investigate the effects of key parameters on ballistic performance. The study’s findings demonstrate that as the volume of the high-pressure chamber increases, the ejection velocity of the UAV is enhanced, but the improvement slows down. Meeting the ejection velocity specifications for the UAV, reducing the volume of the high-pressure chamber can lower the peak pressure within the low-pressure chamber. An increase in the release pressure of the high-pressure chamber can enhance the ejection velocity, but the improvement slows down. Lowering this pressure can effectively reduce the UAV’s acceleration. There is a maximum valve diameter beyond which the ejection velocity remains constant, however, the peak acceleration can still increase. Enlarging the volume of the low-pressure chamber can effectively reduce the UAV’s peak acceleration. This study provides a safe and efficient technical solution for the cold ejection of large UAVs.